Economic and Cultural Drivers of Immigrant Support Worldwide. Issue 4 (1st November 2017) - Valentino, Nicholas A.; Soroka, Stuart N.; Iyengar, Shanto; Aalberg, Toril; Duch, Raymond; Fraile, Marta; Hahn, Kyu S.; Hansen, Kasper M.; Harell, Allison; Helbling, Marc; Jackman, Simon D.; Kobayashi, Tetsuro
Abstract : Employing a comparative experimental design drawing on over 18, 000 interviews across eleven countries on four continents, this article revisits the discussion about the economic and cultural drivers of attitudes towards immigrants in advanced democracies. Experiments manipulate the occupational status, skin tone and national origin of immigrants in short vignettes. The results are most consistent with a Sociotropic Economic Threat thesis: In all countries, higher-skilled immigrants are preferred to their lower-skilled counterparts at all levels of native socio-economic status (SES). There is little support for the Labor Market Competition hypothesis, since respondents are not more opposed to immigrants in their own SES stratum. While skin tone itself has little effect in any country, immigrants from Muslim-majority countries do elicit significantly lower levels of support, and racial animus remains a powerful force.